Review of Challenges Experienced by Women in Subsistence Crop Production - Rankoana, Sejabaledi Agnes (CV. Literasi Indonesia, 2025)
Men and women are assigned roles and obligations that they must fulfill to sustain the welfare of their households. These are adhered to despite the challenges encountered by women, essential food producers within households, to guarantee sustainable food security. This review described the challenges faced by female subsistence crop farmers in securing household food security. The primary research technique adopted is a literature analysis of subsistence production, climate change, its effects, mitigation strategies, and adaptation methods. The review findings indicate that women play a crucial role as subsistence producers of rain-fed crops, notwithstanding the numerous constraints encountered in production systems. The primary challenges include erratic rainfall and sub-optimal crop yield. These obstacles hinder women's ability to fulfill their household food supplier roles. These challenges could be addressed to empower women farmers, augment crop productivity, alleviate rural poverty, enhance food security and nutrition, and encourage women's involvement in food security and climate change mitigation and adaptation. These will facilitate the attainment of several Sustainable Development Goals, namely SDG1 (End Poverty), SDG2 (Zero Hunger), SDG3 (Good Health and Wellbeing), SDG5 (Gender Equality), and SDG13 (Combat Climate Change).